Meller, H., Krause, J. y Risch, R. (2023) Kinship, Sex, and biological relatedness. The contribution of archaeogenetics to the understanding of social and biological relations. 15th Archaeological Conference of Central Germany. Halle 2022. Heidelberg: Propylaeum. 340 páginas. ISBN 978-3-96929-259-4. https://doi.org/10.11588/propylaeum.1280 - Hofmann, Daniela (SPAL - Revista de Prehistoria y Arqueología, 2024)
Reseña de la obra: Kinship, Sex, and biological relatedness. The contribution of archaeogenetics to the understanding of social and biological relations. 15th Archaeological Conference of Central Germany